PORTFOLIO ASSESSMENT AS AN ALTERNATIVE EVALUATION INSTRUMENT IN BASIC PHYSICS LEARNING: A STUDY OF EXPERIMENTAL REPORTS AND STUDENT REFLECTIONS - Sri Agustini; Ahmad Dahlan; Ahmad Yani; Ahmad Swandi (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to examine the implementation of portfolio assessment as an alternative evaluation instrument in the Basic Physics course. The main focus of this study is to analyze the quality of experimental reports and student reflection notes as part of the portfolio, as well as to explore the role of portfolios in supporting more meaningful learning processes. The method used is a quantitative descriptive approach, with the research subjects being 60 students of the physics education study program in the Basic Physics course. Data was collected through portfolio documentation, observations, and in-depth interviews. The results of the study show that portfolio assessment allows students to reflect on their understanding of concepts, compile experimental reports systematically, and show cognitive and metacognitive development more clearly. In addition, reflections written by students indicate an increase in critical thinking skills and learning awareness. Portfolio assessment is considered to be able to provide a more comprehensive picture of student learning outcomes compared to conventional evaluations. Therefore, portfolio assessment is recommended as an evaluation alternative that supports process-based learning and strengthening student competencies in a sustainable manner.